PENGARUH PERTUMBUHAN PERUSAHAAN, OPINI AUDIT SEBELUMNYA DAN PREDIKSI KEBANGKRUTAN TERHADAP OPINI AUDIT GOING CONCERN - Sudarmadi, Sudarmadi (Journal of Information System, Applied, Management, Accounting and Research, 2025)
In performing the monitoring function of a business that is expected to continue to grow and develop so as to avoid difficulties until bankruptcy finally occurs, all stakeholders use financial reports that have been audited by independent auditors and pay attention to the audit opinion given on the financial statements for the sustainability of the company's business and ensure that the financial statements reflect the actual conditions so that they can be used as a basis for making the right decisions. This study aims to determine: (1) The Effect of Company Growth on Going Concern Audit Opinions, (2) The Effect of Previous Audit Opinions on Going Concern Audit Opinions, (3) The Effect of Bankruptcy Predictions on Going Concern Audit Opinions, The Effect of Company Growth, Previous Audit Opinions and Bankruptcy Predictions on Going Concern Audit Opinions empirical study on companies listed on the Indonesia Stock Exchange (IDX) with an observation time of 5 (five) years of observation from the non-premier consumer goods sector listed on the Indonesia Stock Exchange for the period 2017-2021. The results of this study indicate that Company Growth has a positive and significant effect on Going Concern Audit Opinions, Previous Audit Opinions have a positive and significant effect on Going Concern Audit Opinions, Bankruptcy Predictions have no significant effect on Going Concern Audit Opinions, and simultaneously Company Growth, Previous Audit Opinions and Bankruptcy Predictions together or simultaneously have a significant effect on Going Concern Audit Opinions.